Role of mobile food-ordering applications in developing restaurants' brand satisfaction and loyalty in the pandemic period - DİRSEHAN, TAŞKIN (ELSEVIER SCI LTD, 2021)
Retailers and their supply-chain partners should reconsider their competitive advantages in today's technologyenhanced environment and search for opportunities to collaborate. Mobile applications have emerged as a special form of e-commerce that provide convenience for consumers by saving time and effort. In the pandemic days, people prefer using mobile applications in particular to order food from restaurants and protect themselves from COVID-19. Even though there are many previous studies regarding mobile application usage, they have investigated the antecedents of mobile app adoption. Today, consumers already have adopted them, yet there is a need to understand the outcomes of mobile application usage, especially for mobile food-ordering apps (MFOAs). To fill this gap, this study first positions the MFOAs among other mobile food applications regarding their business models. Then, a structural model was developed and tested by focusing on the outcomes of MFOA usage. A survey of 217 participants was conducted, and the data were analyzed using partial least squares path modeling (PLS-PM). The main contribution of the results is the finding that MFOA satisfaction plays a critical role in developing restaurants' brand satisfaction and loyalty. Thus, brands should cooperate with MFOA providers.
Keywords: Food marketing; Mobile food-ordering application (MFOAs); Technology-acceptance model (TAM); Restaurant brand loyalty; TECHNOLOGY ACCEPTANCE MODEL; CUSTOMER SATISFACTION; USER ACCEPTANCE; SERVICE QUALITY; PERCEIVED EASE; INFORMATION-TECHNOLOGY; PLS-SEM; ONLINE; EXTENSION; COMMERCE